2014
DOI: 10.1103/physrevd.90.013021
|View full text |Cite
|
Sign up to set email alerts
|

Near maximal atmospheric neutrino mixing in neutrino mass models with two texture zeros

Abstract: The implications of a large value of the effective Majorana neutrino mass for a class of two texture zero neutrino mass matrices have been studied in the flavor basis. It is found that these textures predict near maximal atmospheric neutrino mixing angle in the limit of large effective Majorana neutrino mass. It is noted that this prediction is independent of the values of solar and reactor neutrino mixing angles. We present the symmetry realization of these textures using the discrete cyclic group Z3. It is f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 113 publications
2
33
0
Order By: Relevance
“…Our results for the textures P 3 and P 4 are compatible with ones [18][19][20][21][22][23][24][25], obtained before. Now we turn to the analysis of the one texture zero neutrino mass matrices we have obtained in Section 3.…”
Section: Predictions From P 1234 Type Neutrino Mass Matricessupporting
confidence: 81%
See 1 more Smart Citation
“…Our results for the textures P 3 and P 4 are compatible with ones [18][19][20][21][22][23][24][25], obtained before. Now we turn to the analysis of the one texture zero neutrino mass matrices we have obtained in Section 3.…”
Section: Predictions From P 1234 Type Neutrino Mass Matricessupporting
confidence: 81%
“…Dirac Yukawa couplings and heavy Majorana neutrino masses) which are not measured so far, a priory it is impossible to make predictions unless some reduction of model parameters are achieved. For this purpose, the texture zero Yukawa and/or Majorana mass matrices have been investigated in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. This approach, besides some predictions, opens up a possibility of relating phase δ (appearing in neutrino oscillations) to the CP asymmetry of the thermal leptogenesis [14][15][16], [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The next step is to draw random points for (sin 2 θ 12 , sin 2 θ 23 , sin 2 θ 13 ) and predict the CP oscillation phase at each draw. Once we get the CP violating phase we can subsitute its value in the functions ∆m 2 12 or ∆m 2 23 and solve for the mass µ 1 . Finally we check if our predictions are consistent with the neutrino allowed regions given by global neutrino oscillation fits [31,32].…”
Section: A Phenomenologymentioning
confidence: 99%
“…According to Dev et al 55 and Meloni et al, 56 we employ the values of θ 23 given for both octant which are shown in TABLE 1.…”
Section: 2017 1:25 Wspc/instruction File Kitabayashi˙ohkawa˙yasue˙mentioning
confidence: 99%
“…[55][56][57][58] This type of matrix is called the two zero flavor neutrino mass texture. If we require a nonvanishing effective neutrino mass M ee for the neutrino less double beta decay, 59,60 only four textures are compatible with observed data in the two zero flavor neutrino mass texture scheme.…”
mentioning
confidence: 99%